VOSviewer: Bibliometric Analysis Tools for Industry 4.0 and Supply Chain - Bambang Niko Pasla; Evi Frimawaty; Iskandar Nasution; Muhammad Dianto; Rangga Almahendra; Ika Sasti Ferina (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: Application of industry 4.0 to support the supply chain in manufacturing by using information and communication technology, a company can optimize integration into the environment, increase production capacity and capabilities, and increase customer value in facing the world of competition in the current era of globalization. The primary purpose of this study is to determine the extent of research on the application of industry 4.0 in the supply chain. Background Problems: Business competition in the manufacturing sector is getting faster and more dynamic. An organization must adapt to environmental changes to innovate to produce a more efficient production system by combining industrial 4.0 technology in a sustainable supply chain by optimizing resources, set-up time, labour costs, materials, production, and product design. Novelty: There is a research gap on logistics and warehouse variables that are not directly connected to industry 4.0 and supply chain management. Research Methods: The method used is a literature review, using bibliometric analysis of the VOSviewer application with data sourced from Scopus. Finding/Results: Found 155 research articles from 2015 to 2022, each year showing significant growth, especially a spike in 2020 to 2021, with 34 research articles. Conclusion: Scientific research related to the application of industry 4.0 in the supply chain in the field of engineering from 2015 to 2022 is increasing, with the direction of research being concentrated on the topic of circular economy, sustainability, cyber-physical system, smart manufacturing, internet of things, block chain, big data, and digitalization.